Pengajian Hadis Era Revolusi Industri 4.0: Isu dan Cabaran: Hadith Studies in the Era of Fourth Industrial Revolution: Issues and Challenges - Muhammad Ammar Shafiq Shahrizal; Siti Nur Balqis Shaharudin; Nurul Auni Hafifah Md Arif; Nur Najiyah Muhamad Yusoff; Abdulloh Salaeh (Maʿālim al-Qurʾān wa al-Sunnah, 2024)
Digital technology advancements have driven the Fourth Industrial Revolution, posing new challenges to various sectors worldwide, including Islamic Studies, particularly in the study of Hadith. Since the outbreak of the COVID-19 pandemic, online Hadith education has become increasingly prominent, as teachers across the country have turned to virtual platforms due to Malaysia's movement control orders. The main issues and challenges that have arisen involve the continuity and preparedness of students in facing these drastic changes. This study aims to identify the issues and challenges encountered in Hadith studies during the Fourth Industrial Revolution. It also seeks to develop a discipline capable of fostering global human capital in line with technological, communication, and scientific advancements, which are now crucial elements in Hadith studies. The research employs a qualitative methodology, with focus group interviews as the primary data collection tool. Despite the potential for global expansion of this technology, the findings reveal that students' ability to adapt to automated teaching methods remains a dominant challenge in Hadith education. Overall, this study provides valuable insights for the government and educational institutions in identifying the best strategies to overcome challenges in the era of the Fourth Industrial Revolution.